Faktoren von Frequenz und Produktivität von Diminution in frühen Dialekterhebungen des Deutschen - Lea Schäfer (Zeitschrift für Wortbildung)
This paper examines the productivity of diminution – mainly on the noun – in two large-scale surveys of German dialects of the 19th and early 20th centuries. The starting point is the basic question whether German dialects use differently dimintutive suffixes and which dialect uses diminutives more frequently than others. In addition to morphological and semantic aspects, this question is linked to numerous sociolinguistic, methodological, and phonotactic factors. This leads for example to the general problem, to what extent dialect stereotypes influence classical dialect surveys.